2020
DOI: 10.1002/best.202000087
|View full text |Cite
|
Sign up to set email alerts
|

Bewertung von Bestandsbauwerken mit gemessenen Daten, Teil 2

Abstract: Durch die Einbeziehung von gemessenen Daten bei der Bewertung von bestehenden Bauwerken können Unsicherheiten bei der Beurteilung des Tragverhaltens reduziert werden, ohne das normative Zuverlässigkeitsniveau einzuschränken. Informationen sind die wesentliche Grundlage für die Analyse der Zuverlässigkeit von Tragwerken. Umso wichtiger ist die Kenntnis über die Präzision und die Richtigkeit der verwendeten Informationen. Aus messtechnischer Sicht kann ein Messwert, dem keine Messunsicherheit beigeordnet wurde, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…With focus on the investigation of the structure, practical examples for the use of data in the reassessment process were published in [2,29,30]. Structural inspection processes are, e.g., the localization of rebars and tendons, the determination of the cross-sectional thickness, the estimation of concrete strengths, the detection of corrosion or the investigation of the injection status and of the applied forces to the tendons.…”
Section: Use Of Full-probabilistic Methods For the Analysis Of The Ba...mentioning
confidence: 99%
See 1 more Smart Citation
“…With focus on the investigation of the structure, practical examples for the use of data in the reassessment process were published in [2,29,30]. Structural inspection processes are, e.g., the localization of rebars and tendons, the determination of the cross-sectional thickness, the estimation of concrete strengths, the detection of corrosion or the investigation of the injection status and of the applied forces to the tendons.…”
Section: Use Of Full-probabilistic Methods For the Analysis Of The Ba...mentioning
confidence: 99%
“…Figure 11 displays the results of a sensitivity analysis of the load bearing capacity for shear and bending moment of an existing bridge based on measured data. The numbers in brackets display the change compared to the results of the sensitivity analysis without the implementation of the measurement data, see [30]. As seen on the left side, the sensitivity of the distance of shear reinforcement changes significantly with the implementation of the on-site results.…”
Section: Use Of Full-probabilistic Methods For the Analysis Of The Ba...mentioning
confidence: 99%
“…The limit state functions are formulated to include as many measurable data as possible. While a number of limit state functions for current design equations are available in literature [10][11][12], the former design equations of the codes from the time of construction and from previous codes still need to be formulated as limit state equations for fullprobabilistic calculations. The loads and reactions from the finite element models are converted from characteristic values to mean values and a fully probabilistic calculation is performed based on the transformed results from the finite element models and with accepted distribution parameters from literature, e.g., provided by the Joint Committee on Structural Safety.…”
Section: Limit States and Calculation Principlesmentioning
confidence: 99%
“…Further information about the case-study outlined above can be found in [11]. A second study dealing with ultimate limit states was published in [18,19].…”
Section: Demonstration -Measurement Uncertainty In Structural Reliabi...mentioning
confidence: 99%